Etika Pertukaran Valas Dalam Pasar Valuta Asing Perspektif Fikih Sarf - Bakhrul Huda (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
A certainty foreign exchange is not currently as an escape of sharia economic subject specialist moreover in the foreign exchange market practicing. The variants of sport, future, and option have been examining the validity of sharia’s law by referencing on Fikih Sarf (jurisprudence’s banking). The stakeholder of fatwa has also issued his fatwa on it. The writer tries to analyze and understand of fatwas by exploring classical and contemporary literacy, especially based on the relationship of ethical exchange in which becomes the main element on Fikih Sarf. It purposes to increase the existing literacy insights and facilitated the next researcher, because many of fatwas is less detail understanding. Based on what analyzed by writer can be concluded that foreign exchange ethic must be intended to satisfy the needs, do not make money as a commodity trade which effects a bubble economy on the endanger economy of derivative market as predicted on forex online.